Stationary waves in the wintertime mesosphere: Evidence for gravity wave filtering by stratospheric planetary waves. Issue 8 (25th April 2013) - Lieberman, R. S.; Riggin, D. M.; Siskind, D. E.
Abstract : [1] Quasi‐stationary planetary‐scale waves in the wintertime mesosphere and lower thermosphere (MLT) are thought to be forced in part by drag imparted by gravity waves that have been modulated by underlying stratospheric waves. Although this mechanism has been demonstrated numerically, there have been very few observational studies that examine wave driving as a source of planetary waves in the MLT. This study uses data from EOS Aura and TIMED between 2005 and 2011 to examine the momentum budget of MLT wintertime planetary waves. Monthly averages for January indicate that the dynamics of zonal wave number 1 are determined from a three‐way balance among the Coriolis acceleration, the pressure gradient force, and a momentum residual term that reflects wave drag. The MLT circulations in January 2005, 2006, 2009, and 2011 are qualitatively consistent with a simple model of wave forcing by drag from gravity waves that have been modulated by stratospheric planetary waves. MLT winds during these years are also consistent with analyses from a high‐altitude operational prediction model that includes parameterized nonorographic gravity wave drag. The importance of wave drag for the MLT momentum budget suggests that the gradient wind approximation is inadequate for deriving planetary‐scale winds from global temperature measurements. Our results underscore the need for direct global wind measurements in the MLT. Key Points: Mesospheric planetary waves (PW)are ageostrophic. PW in the MLT have in-situ and stratospheric sources. MLT PW winds indicate forcing by longitudinally variable gravity‐wave drag.